2018
DOI: 10.1097/brs.0000000000002708
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Full-endoscopic Decompression via Interlaminar Approach for Central or Lateral Recess Spinal Stenosis of the Lumbar Spine

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 25 publications
3
86
0
Order By: Relevance
“…Multiple studies 27,34,40,45,49,56 have demonstrated that endoscopic lumbar decompression in the setting of LSS provides equivalent outcomes to microsurgical or tubular techniques with shorter hospital stay and less collateral tissue injury. 2,40,41,47 The purpose of this study was to evaluate and compare the clinical efficacy of LE-ULBD and MIS-ULBD decompression in patients with LSS and coexisting degenerative deformity.…”
mentioning
confidence: 99%
“…Multiple studies 27,34,40,45,49,56 have demonstrated that endoscopic lumbar decompression in the setting of LSS provides equivalent outcomes to microsurgical or tubular techniques with shorter hospital stay and less collateral tissue injury. 2,40,41,47 The purpose of this study was to evaluate and compare the clinical efficacy of LE-ULBD and MIS-ULBD decompression in patients with LSS and coexisting degenerative deformity.…”
mentioning
confidence: 99%
“…As a result, the prevalence of degenerative LSS is increasing.However, chronic pain and discomfort from LSS may signi cantly impair psychosocial function and induce sleep disorders, depressive symptoms, and increased utilization of health care (12). In recent years, PE has become the most minimally invasive treatment for lumbar degenerative disease, its indications are constantly being expanded, and it has proven e cacy for LSS (10,13). For elderly patients with LSS, while traditional surgical treatment can achieve extensive decompression and pain relief, it is associated with high risk and long recovery before resuming normal activities, and it takes longer to improve the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic laminectomy has been shown to have equal long-term outcomes when compared with open surgery with the potential for decreased postoperative pain, complications, and hospital length of stay. 10,12,13 Second, the study lacks a comparison group that underwent lumbar laminectomy via open or tubular means. However, the objective of this study was not to demonstrate the superiority of endoscopy over open or tubu-lar approaches, or vice versa.…”
Section: Discussionmentioning
confidence: 99%